Robert Ludlum's The Bourne sanction : a new Jason Bourne novel - Lustbader, Eric (Lustbader, Eric. New Jason Bourne novel., 2008)
"Jason Bourne must confront a nightmare version of himself--an amoral, heartless killer--in this new novel in Robert Ludlum's bestselling series"--Provided by publisher.